2014
DOI: 10.1093/toxsci/kfu060
|View full text |Cite
|
Sign up to set email alerts
|

2-Amino-1-methyl-6-phenylimidazo[4,5-b]pyridine (PhIP) Is Selectively Toxic to Primary Dopaminergic Neurons In Vitro

Abstract: Parkinson's disease (PD) is the second most common neurodegenerative disease. Much data has linked the etiology of PD to a variety of environmental factors. The majority of cases are thought to arise from a combination of genetic susceptibility and environmental factors. Chronic exposures to dietary factors, including meat, have been identified as potential risk factors. Although heterocyclic amines that are produced during high-temperature meat cooking are known to be carcinogenic, their effect on the nervous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(52 citation statements)
references
References 50 publications
0
52
0
Order By: Relevance
“…However, humans consume numerous HCAs (~30 known, likely many unknown) vs. PhIP alone, suggesting that considering dietary intake of a single HCA underestimates total HCA consumption (Augustsson et al , 1997; Roemer et al , 2016). Further, our previous studies found that of the two primary metabolic pathways, the N -hydroxylation product is far more neurotoxic than ring-hydroxylation (Griggs et al , 2014). N -hydroxylation is at least 13-fold less efficient in rodents vs. humans (rodent CYP1A2 converts far more PhIP to 4′-OH-PhIP than to the genotoxic and neurotoxic N -hydroxylated metabolite, N -OH-PhIP), suggesting that far higher doses may be required in rodents vs. humans to produce neurotoxic metabolites (Cheung et al , 2005; Griggs et al , 2014; Turesky et al , 1998).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, humans consume numerous HCAs (~30 known, likely many unknown) vs. PhIP alone, suggesting that considering dietary intake of a single HCA underestimates total HCA consumption (Augustsson et al , 1997; Roemer et al , 2016). Further, our previous studies found that of the two primary metabolic pathways, the N -hydroxylation product is far more neurotoxic than ring-hydroxylation (Griggs et al , 2014). N -hydroxylation is at least 13-fold less efficient in rodents vs. humans (rodent CYP1A2 converts far more PhIP to 4′-OH-PhIP than to the genotoxic and neurotoxic N -hydroxylated metabolite, N -OH-PhIP), suggesting that far higher doses may be required in rodents vs. humans to produce neurotoxic metabolites (Cheung et al , 2005; Griggs et al , 2014; Turesky et al , 1998).…”
Section: Methodsmentioning
confidence: 99%
“…Of dietary HCAs, 2-amino-1-methyl-6-phenylimidazo[4,5-b]pyridine (PhIP) has been extensively studied, because PhIP is the most abundant AIA isolated from the crust of cooked meat, where levels may reach ~15 micrograms/kg uncooked meat (~75% of genotoxic material) (Felton et al , 1986a; Felton et al , 1986b) While PhIP has been extensively studied as a mutagen, effects on the nervous system have not yet been substantially evaluated. Recently, our group showed that PhIP is selectively toxic to dopaminergic neurons in primary rat midbrain cultures (Griggs et al , 2014). In that study, PhIP and its bioactive phase I metabolite, N -OH-PhIP induced loss of dopaminergic neurons and neurite retraction, whereas nondopaminergic neurons were spared.…”
Section: Introductionmentioning
confidence: 99%
“…K. Turteltaub and A. Director-Myska). Recent neurotoxicity studies on PhIP in vitro using primary midbrain cultures have been performed [ 192 ]. PhIP and N-OH-PhIP treatments at 1 μ M were selectively toxic to primary dopaminergic neurons isolated from embryonic day 17 rat embryos.…”
Section: Byproducts Of Preparationmentioning
confidence: 99%
“…There are some outliers which strongly influenced the mean, with sample size being 71, 184, and 694. The paper which employed large sample sizes of 184 and 694 were about neurotoxicity of heterocyclic amines but the definition of sample number were not conventional (number of neurites for the outcome measurement of neurite length, and mean pixel intensity in the regions of interests) (32) while the one used the average sample size of 71 were about the neurotoxicity of flame retardants and the sample number is the number of wells (of 96 well plate) per group (22) . Besides these few outliers, most studies have small sample sizes, raising a concern that the studies may be underpowered to conduct inferential statistics and the dispersion of data might not indicate the true distribution of the underlying distribution of the outcome variables.…”
Section: Resultsmentioning
confidence: 99%